A framework for comparing entrepreneurship processes across nations - Baker, Ted; Gedajlovic, Eric; Lubatkin, Michael (Journal of International Business Studies, 2005)
Shane and Venkataraman's Discovery, Evaluation and Exploitation entrepreneurship framework ignores issues central to comparative international entrepreneurship (IE) because of unnecessarily under-socialized assumptions regarding entrepreneurial opportunities and the individuals who discover them. To better promote comparative IE research, we develop a Comparative Discovery, Evaluation and Exploitation framework (CDEE), which takes as a starting point that individuals motivated by diverse goals enact market opportunities in a variety of social settings. Building on this characterization, the paper explores how and why processes of opportunity discovery, evaluation and exploitation vary across and within nations, as well as the implications of these differences.